Development Of Students' Speech - Usarov Ravshan Khudaiarovich (Global Scientific Publishing, 2025)
The development of students' speech is the most important task of teaching the Russian language. Work on speech development is carried out in all lessons of the school course of the Russian language and in special lessons of coherent speech development, where certain communicative and speech skills are practiced in accordance with the program. The formation of oral and written speech skills is carried out in the lesson.
Keywords: Speech development; special lessons of coherent speech development; in oral or written speech